HUBUNGAN FISIK RUMAH DENGAN KEJADIAN ISPA PADA BALITA DISEKITAR USAHA PEMBUATAN BATU BATA DI DESA TANJUNG MULIA KECAMATAN PAGAR MERBAU KABUPATEN DELI SERDANG TAHUN 2013 - putri ruth ras meita; nurmaini *; surya dharma (Lingkungan dan Kesehatan Kerja, 2014)
Acute Respiratory Infection (ARI) is a major health problems in indonesia. Based on data from Puskesmas Bandar Dolok, ARI was in first rank from ten biggest disease in Puskesmas Bandar Dolok. ARI attacks many children. ARI may caused by bad physical condition of dwelling house. The dwelling house in Desa Tanjung Mulia mostly around over the brickyard and less of health condition.This study aimed to determine the relationship among the physical condition of dwelling house, ventilation, natural lighting, humidity, wall, floor and ceiling with the incidence of Acute Respiratory Infection to the children under-five years old in Desa Tanjung Mulia Kecamatan Pagar Merbau Kabupaten Deli Serdang on 2013.The type of this study was descriptive analytic by cross sectional design. The sample of this study was 60 chidren under-five years old who live around the brickyard taken by quota sampling. 60 sample consist of 44 children under-five years old with ARI and 16 is had not symptom of ARI.The results showed that there was significant relationship between the ventilation with the incidence of Acut Respiratory Infections in children under-five years old (p=0,026). Meanwhile, there was no relationship between the natural lighting (p=0,263), the humidity (p=1,000), the floor (p=1.000), the wall (p=0.967) and the ceiling (p=1.000) with the incidence of Acut Respiratory Infections in children under-five years old.It is suggested to community who lived in Desa Tanjung Mulia Kecamatan Pagar Merbau Kabupaten Deli Serdang to make good house ventilation and to plant plants as dust barricade. It is suggested to public health official to give health promotion about the house healthy condition, in order to prevent respiratory diseases.Keywords : House physical condition, Children under-five years old, Acute Respiratory Infection